Phase Alignment With Minimum Complexity for Equal Gain Combining in Multi-Aperture Free-Space Digital Coherent Optical Communication Receivers - Yicong Tu (IEEE Photonics Journal, 2020)
Digital coherent combining (DCC) technique can increase the free space optical signal collection area by combining the signals received by an array of small apertures in a coherent manner. To realize DCC the different versions of signals must be aligned in phase by the digital phase alignment algorithm (PAA). Low computation complexity is imperative for the PAA because the main obstacle to implement the PAA and DCC in a real-time manner is the availability of digital signal processing (DSP) circuits offering very high gate density and processing speed. In this paper we investigate the relationship between the computation complexity, optical phase offset estimation error and the combining loss for the equal gain combining technique. Analytical expressions are deduced allowing easy minimization of the computation complexity at an arbitrary input OSNR and acceptable combining loss. Extensive numerical simulations are carried out to validate the analytical expressions.